Farmer producers’ organizations in Karnataka with respect to neera production in coconut (Cocos nucifera)–a case study - Prabhat Kumar; Hanumanthe Gowda B; Leenamol MA (Current Horticulture, 2025)
The study investigated the success rate of Kalparasa [a fresh, unfermented, nutritious health drink obtained from the inﬂorescence of coconut (Cocos nucifera L)], which emerged as an innovative method to generate income from coconut palms. The company, Kalparasa Coconut and All Spices Producers Company Limited, was established and has beneﬁted a large number of coconut growers in Karnataka, as well as other states like Jharkhand, Odisha, and Assam. In the current ﬁnancial year, each palm yielded 400-600 liters of Kalparasa, with the participation of 6,800 farmers as shareholders and 19 farmers speciﬁcally involved in neera collection. The company has increased its turnover from Rupees 6.18 lakhs in 2021–22 to Rupees 22.69 lakhs in 2022–23.